(untitled) (International Journal of Environmental Sciences, 2025)
In meteorology, the planetary boundary layer (PBL), often called the atmospheric boundary layer (ABL), is the lowest layer of the atmosphere. Its behavior is dictated by its direct contact with a planetary surface. On Earth, it usually responds to variations in surface radiative forcing in less than an hour. Intense vertical mixing and rapid variations in physical parameters including flow velocity, temperature, and moisture are present in the lowest layer. The wind is affected by surface drag and spins across the isobars in the open atmosphere above the PBL, where it normally flows parallel to the isobars. The European Centre for Medium-Range Weather Forecasts (ECMWF) collected data on temperature, dew point, atmospheric pressure, and height from satellites for height (32-26509.7) m, pressure levels (1000-20) mbar, and the selection of characteristic days of the month of 2018 for the Baghdad station to obtain the greatest number and variety of clouds and their use in the calculation of cloud cover and weather stability in terms of calculation daily change. To define the type of air stability, the potential temperature (ɵ) was also computed with height. Atmospheric stability was also estimated with the height of the cloud base and below the cloud base. The findings demonstrated that throughout the seasons, the atmosphere is either stable (St), unstable (UnSt), or neutral (Neu).